Antioxidative and EROD activities of osajin and pomiferin - Veselá, Dagmar; Kubínová, Renáta; Muselík, Jan; Zemlicka, Milan; Suchý, Václav (Fitoterapia, 2004)
The major constituents of fruits of Maclura pomifera are the prenylated isoflavones, osajin (1) and pomiferin (2). Since significant biological activities of extracts from the wood of M. pomifera were previously reported, the peroxynitrite scavenging activity, inhibition of lipid peroxidation, scavenging of DPPH and EROD activity of these two major substances were studied.
Keywords: Benzopyrans; scavengery volných radikálů; lidé; Phytotherapy; benzopyrany; Biphenyl Compounds; Fruit; ovoce; cytochrom P-450 CYP1A1; rostlinné extrakty; Lipid Peroxidation; bifenylové sloučeniny; isoflavony; fytoterapie; Peroxynitrous Acid; Picrates; Isoflavones; Humans; Free Radical Scavengers; Maclura; kyselina peroxydusitá; pikráty; Plant Extracts; peroxidace lipidů; Cytochrome P-450 CYP1A1